2007
DOI: 10.1080/00103620601094213
|View full text |Cite
|
Sign up to set email alerts
|

Soil Evaporation and its Affecting Factors under Crop Canopy

Abstract: Based on field experiments, changing patterns and affecting factors of soil evaporation and energy balance under crop canopy were studied. Soil evaporation under crop canopy was measured directly using the microlysimetry technique. The main factors affecting soil evaporation under crop canopy including surface net radiation, leaf area index, soil water content, and crop growth period were analyzed to give scientific proof for the soil evaporation control. The results showed that no soil evaporation occurred un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Note that T g is used rather than T s , because this allows for shortwave radiation to control the soil evaporation. In forest regions, a high leaf area reduces shortwave radiation penetrating to the ground surface, reduces T g , and reduces soil evaporation (Wang & Liu, 2007). In many LSMs, alpha is defined by the Council (NERC) through the DTP in Environmental Research (Grant NE/L002612/1).…”
Section: Appendix A: Evaporation Partitioning In Lsmsmentioning
confidence: 99%
“…Note that T g is used rather than T s , because this allows for shortwave radiation to control the soil evaporation. In forest regions, a high leaf area reduces shortwave radiation penetrating to the ground surface, reduces T g , and reduces soil evaporation (Wang & Liu, 2007). In many LSMs, alpha is defined by the Council (NERC) through the DTP in Environmental Research (Grant NE/L002612/1).…”
Section: Appendix A: Evaporation Partitioning In Lsmsmentioning
confidence: 99%
“…4) was majorly due to crop factors such as shoot and root growth. Wang and Liu (2007) reported that leaf area index (LAI) influences evaporation, actually, SB20 variety as an example in the current experiment had high shoot and root biomasses (Omondi et al, 2014) and hence high LAI which reduced evaporation. However, the gains in soil moisture content through canopy cover were negated by the absorption of more moisture to sustain this heavy vegetative growth and increased transpiration.…”
Section: Crop Evapotranspirationmentioning
confidence: 99%
“…This led to the overall decline in soil moisture under SB20 (Table 2) Arnold et al (2015) and Yan et al (2014) also reported the influence of minimum canopy as the cause for increased evaporation. Evaporation as a factor of ETc had minimum fluctuation as it is dependent on solar radiation (Wang and Liu, 2007). The days when the slope of the relationship between ET 0 and ET C were negative (Fig.…”
Section: Crop Evapotranspirationmentioning
confidence: 99%
“…Ground-level light intensity corresponds negatively with corn growth, leading to an increasingly shady and cool sub-canopy environment. Furthermore, Wang and Liu demonstrate that soil evaporation decreases exponentially in relation to leaf area index until hitting zero, at a sub-canopy radiation level of 230.57 watts per m 2 [42].…”
Section: Adequacy Of Red Clover For the Proposed Systemmentioning
confidence: 99%
“…Cover crops also moderate soil moisture conditions by interrupting the soil surface, preventing direct soil-raindrop impact, and thus preventing crusting and sealing and improving water infiltration and retention [70]. Although cover crops contribute to systemic water loss through transpiration, Wang and Liu note that transpiration contributes to total agroecosystem productivity, whereas soil evaporation is lost from the system [42]. Thus, in the proposed system, red clover offers agro-ecological benefits that bare soil cannot.…”
Section: Regulating Soil Conditionsmentioning
confidence: 99%